Advance Organizer Model and Its Effectiveness on Junior High School Students’ Writing Accuracy - Djonga, Junus Ludji; Musyarofah, Lailatul; Taufik, Kani Sulam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effect of the advance organizer model on the accuracy of students' writing. It used a single-group pretest-posttest design, which allowed for a pre-experimental design, with 9th grade students from SMP Negeri 5 Menia as participants. The statistical technique used to analyze the data was analysis of covariance (ANCOVA). At the 0.05 level of significance, the hypotheses were tested. The data in the tables t-Test: Paired Two Sample for Means (9-A) reveals that the obtained t-value was 13.276, which was significantly higher than the threshold value of 0.05. The post-test, on the other hand, had a mean of 78.91. Due to the fact that the p-value was less than the 0.05 standard level of significance, the researchers can reject the null hypothesis (Ho). Thus, the second hypothesis (Ha) was accepted, indicating that the advance organizer model had a significant effect on studentsâ€™ writing. It is recommended that English teachers use this model to help students improve their writing ability. For students, it is suggested that they pay closer attention to the teaching model being used, such as implicit and explicit grammar instruction through the advance organizer model, so they can also explore their writing ability. Other studies, on the other hand, should investigate the effect of alternative organizers on specific writing genres or use advance organizer in combination with other research methods such as mix-method. Â